Neuronal organization of olfactory bulb circuits - Nagayama, Shin; Homma, Ryota; Imamura, Fumiaki (Frontiers in Neural Circuits, 2014)
Olfactory sensory neurons extend their axons solely to the olfactory bulb, which is dedicated to odor information processing. The olfactory bulb is divided into multiple layers, with different types of neurons found in each of the layers. Therefore, neurons in the olfactory bulb have conventionally been categorized based on the layers in which their cell bodies are found; namely, juxtaglomerular cells in the glomerular layer, tufted cells in the external plexiform layer, mitral cells in the mitral cell layer, and granule cells in the granule cell layer. More recently, numerous studies have revealed the heterogeneous nature of each of these cell types, allowing them to be further divided into subclasses based on differences in morphological, molecular, and electrophysiological properties. In addition, technical developments and advances have resulted in an increasing number of studies regarding cell types other than the conventionally categorized ones described above, including short-axon cells and adult-generated interneurons. Thus, the expanding diversity of cells in the olfactory bulb is now being acknowledged. However, our current understanding of olfactory bulb neuronal circuits is mostly based on the conventional and simplest classification of cell types. Few studies have taken neuronal diversity into account for understanding the function of the neuronal circuits in this region of the brain. This oversight may contribute to the roadblocks in developing more precise and accurate models of olfactory neuronal networks. The purpose of this review is therefore to discuss the expanse of existing work on neuronal diversity in the olfactory bulb up to this point, so as to provide an overall picture of the olfactory bulb circuit.